Onda de densidad de carga y superconductividad en ta1-xmoxs2 : evolución de propiedades estructurales y electrónicas (2021)
Transition metal dichalcogenides are a family of quasi-two-dimensional quantum materials with a unique susceptibility to the variation of parameters such as pressure, chemical doping, disorder, etc. These materials have been widely studied due to the great variety of base states they can display. Of special interest are the compounds of this family that show superconductivity and charge density wave (CDW), since the exact mechanism for stabilizing and optimizing superconductivity in systems showing these two fundamental states is still an open question. In this work, we study the evolution of the electronic and structural properties of single crystals of the solid solution Ta1-xMoxS2, where TaS2 is a metal with the presence of CDW at low temperatures, and MoS2 is a semiconductor, both systems belonging to the family of transition metals dichalcogenides. From X-ray diffraction measurements and electrical transport measurements, we evidenced a slight suppression of the charge density wave temperature, with respect to TaS2, as well as a significant increase in the critical superconductivity temperature for low doping in which predominates the 2H (trigonal prismatic) structural phase. For intermediate doping, we observed the presence of other structural phases in addition to 2H, as well as wide superconducting transitions but with a high onset temperature similar to that observed for low doping.